The Ottoman scramble for Africa empire and diplomacy in the Sahara and the Hijaz - Minawi, Mostafa (Stanford University Press, 2016)
A history of the Ottoman participation in colonial expansion in Africa in the last 20 years of the 19th century, this book turns the spotlight onto the Ottoman Empire's experiment in "new imperialism."